The Implications of Gated Society in Jakarta Metropolitan Region: A Multiple-Case Study in Tangerang District, Banten, Indonesia - INDAH SURYA WARDHANI (Universitas Muhammadiyah Yogyakarta, 2016)
This paper argued that the gating system intensifies existing divergence of the gated communities and the kampung communities. The significant dissimilarities between the residents and the dwellers strongly indicate social inequality. The notion of gated society at the neighborhood level remains problematic. The existence of fortress raises some ethical questions whether the rich, the high-level professional, and the famous have right to fort to themselves and keep other citizens out, whether they have privilege to set the boundaries and live separately from society as well as maintain the amenities exclusively. The gated society inevitably brings enormous policy consequences. This paper recommend housing policy as social legislation to regulate the notion of gated society. The long term practices of exclusion within fortress, and public space privatization will impede the function and very idea of the future citizenship. Beyond social redistribution, the principle idea of housing policy is promoting inclusive right for sustainable development. The absence of theinclusiveness results in a decline of democracy.Keyword: gated community, social segregation, inequality, housing policy, citizenship